2020
DOI: 10.3390/ma13225084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drying Shrinkage of Concrete Specimens Recycled Heavyweight Waste Glass and Steel Slag as Aggregate

Abstract: This study analyzed the fundamental properties of concrete using steel slag, to test its viability as an aggregate material. An experimental investigation into the effect of steel slag as a coarse aggregate, and heavyweight waste glass as a fine aggregate, on the drying shrinkage of concrete was performed. The calculated shrinkage strain was compared to five different shrinkage prediction models, namely, the ACI 209, B3, KCI 2012, EC 2 and GL 2000 model codes, to evaluate their ability to accurately predict sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The use of steel slag as a partial replacement for cement could make a significant contribution to the steel industry and help to reduce CO 2 emissions [17]. The partial replacement of cement by various steel and blast furnace slags was also recently reported [18][19][20]. Li et al [21] studied the effects of steel slag and expansive agents on the properties of ultrahigh performance concrete, and they stated that 15% slag and 5% expansive agents are required proportions to produce a good quality of targeted concrete.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of steel slag as a partial replacement for cement could make a significant contribution to the steel industry and help to reduce CO 2 emissions [17]. The partial replacement of cement by various steel and blast furnace slags was also recently reported [18][19][20]. Li et al [21] studied the effects of steel slag and expansive agents on the properties of ultrahigh performance concrete, and they stated that 15% slag and 5% expansive agents are required proportions to produce a good quality of targeted concrete.…”
Section: Introductionmentioning
confidence: 98%
“…Selected studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] of numerous recent research works reported to the scientific journal Materials were devoted to the use and incorporation of steel slags in road construction materials and concrete. The BOF slag incorporated in the asphalt mixture is advantageous for improving the ability of this mixed material to resist the deformation and enhancing the stability of structure, according to Ye et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers are working on various admixtures to improve the performance of concrete. Fly ash and blast furnace slag are widely known admixture materials to replace cement [1][2][3], and some researchers used industrial wastes such as waste glass and steel slag to replace aggregates [4][5][6]. Recently, studies on materials that can improve the performance of cement composites by using small amounts are being conducted [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high content of CaO in slag, it is a suitable substitute material for concrete. However, steel slag also contains free-CaO [30], which can be detrimental to the volumetric stability of concrete if the free-CaO content exceeds 2% [34]. The volume stability decreases as the free-CaO reacts with water to form calcium hydroxide, increasing the volume by up to 98% [35].…”
Section: Introductionmentioning
confidence: 99%